Aprendizagem colaborativa com apoio computacional: uma experiência no ensino fundamental - Lima, Mixilene Sales Santos (2015)
The perspectives of the Computer-supported Colaborative Learning and the Mobile Learning brings on propitious elements to students colaborative learning inside or outside the classroom. In this context, the present work discuss the colaborative learning supported by mobile devices. The research aimed to investigate the computer-supported colaborative work of primary school students, from the analysis of a project titled Sustentable Conscious: Walking to a better world, experienced by 7th to 9th grade students of a Public School from Ceará, who have made use of mobile devices and applications throughout colaborative activities. The Research has qualitative character and features as an intervention research. The tools and techniques of seizure of data comprises notebook notes, videos, audios, pictures and interviews to register how the computer-supported colaborative work develops itself. The results are analysed according to categories and subcategories stablished during the data analysis. The first category, Intervention, is detailed by how the researcher participation contributed to the development of the intervention project and how students get envolved in the project activities. The second one, Mobile Learning, concerns the devices mobility explored by students during the intervention project, identifying how this mobility influences in colaborative practices of the class. The next one, Colaborative Application, it is verified how happens the use of applications by stutents and how their functionalities are used in favour of the group work. The last one, Computer-supported Colaborative Learning, presents itself in how students performed the colaborative productions, the group discussions, the ideias negociation and the colaborative work, detailing how these moments happens. The results highlights situations that characterizes how the Mobile Devices-supported Colaborative Learning can happen and show that colaborative learning can occur through applications and expands itself beyond the classroom spaces with the use of netbook and smartphone, in favour of students mobility, since a planned pedagogic intervention is performed in order to optimize the available resources in mobile devices.